MANIPULASI TERHADAP AKTA JUAL BELI ATAS TANAH HAK GUNA BANGUNAN DI ATAS TANAH HAK PENGELOLAAN (BERDASARKAN PUTUSAN MAHKAMAH AGUNG NOMOR 239 PK/PDT/2018) - Muhammad Razaq; Flora Dianti (JURNAL DARMA AGUNG, 2023)
Land rights refer to the entitlement of an individual to use or benefit from a specific piece of land. The transfer of building use rights and land management rights from the developer to the buyer is only possible if the buyer fulfills all necessary requirements. However, a study was conducted to understand the legal implications of manipulating the Deed of Sale and Purchase and the consequences of not extending land use rights. The research used normative methods and secondary data to draw conclusions. The study revealed that Defendants I and II committed an illegal act by deliberately infiltrating the Management of the Association of Residents of Flats, which violated the subjective rights of others and moral rules. The ownership status of the plaintiff's land was lost due to the change in status from Building Use Right to Management Rights, which is a right of use owned by the DKI Regional Government. The study emphasizes the importance of complying with legal requirements to avoid legal consequences.